Влијанието на ортоптичкиот третман во лекувањето на дивергентно-интермитентните страбизми - Димитрова Радојичиќ, Даниела (Филозофски факултет, Скопје, 2000)
Orthoptic treatment of intermittent divergent strabismus is one of the important methods of treat of this strabismus. The treatment can be a simple action and complicated orthoptic-pleoptic excesses which searching a special condition and special equipment. Our examination had a task to notice the effect of this treatment on the rehabilitation of binocular sight, that mean stabilization of binocular relationship, which in specific cause can determined a functional recover, or in case that is impossible it can be a prepare for a operation. We can execute the following conclusion from our examination: that after the application of orthoptic treatment was an evident improvement in binocular relationship in the patient with intermittent divergent strabismus.
Keywords: intermittent divergent strabismus, orthoptic treatment, amblyopic, angle of deviation, abduction and adduction, and range of motor fusion